In vitro Antibacterial and in vivo Antinociceptive Activities of Ethyl Acetate Fraction of Dipterocarpus turbinatus Leaves - Akter, Nasrin; Sayeed, Mohammed Abu; Jahan, Israt; Habib, Nawara; Ullah, Mohammad Hamid; Arman, Mohammad (Bangladesh Pharmaceutical Journal, 2024)
The study was aimed to assess the antibacterial and analgesic properties of the ethyl acetate extract from the leaves of Dipterocarpus turbinatus. The antibacterial effectiveness of the extract obtained from the leaves of D. turbinatus was evaluated using the disc diffusion method against both positive and negative Gram strains. Furthermore, the analgesic qualities were assessed by doing the formalin-incited paw licking test in mice model. The ethyl acetate fraction demonstrated significant antibacterial activity against all tested microorganisms (Lactobacillus casei, Corynebacterium sp., Bacillus cereus, Staphylococcus aureus, Escherichia coli, Bacillus azotoformans, and Salmonella typhi) at concentrations of 0.1 mg/disc, 0.3 mg/disc, and 0.5 mg/disc using the disc diffusion method. The extract's zone of inhibition measured between 12 and 25 mm was less than the Kanamycin's diameter of 32–36 mm. The analgesic activity of the substance was evaluated in Swiss Albino mice using the tail immersion and formalin test procedures, revealing a modest level of analgesic activity. In the formalin test, the extract had a strong dose-dependent impact at dosages of 200 mg/kg and 400 mg/kg, as shown by a larger inhibition percentage compared to the standard. This result was statistically significant (***p<0.001) when compared to the control group. During the tail immersion test, the extract showed a significant impact at dose 400 mg/kg (**p<0.01). The plant extract has a modest level of antibacterial and analgesic properties. Bangladesh Pharmaceutical Journal 27(2): 207-214, 2024 (July)